The Role of Toll-Like Receptor-2 in Clostridioides difficile Infection: Evidence From a Mouse Model and Clinical Patients - Lai, Yi-Hsin; Tsai, Bo-Yang; Hsu, Chih-Yu; Chen, Yi-Hsuan; Chou, Po-Han; Chen, Yueh-Lin; Liu, Hsiao-Chieh; Ko, Wen-Chien; Tsai, Pei-Jane; Hung, Yuan-Pin (Frontiers in Immunology, 2021)
Background: Clostridioides difficile is the leading cause of nosocomial infectious diarrhea. Toll-like receptors (TLRs) are the major components of innate immunity that sense pathogens. The relationship between TLRs and C. difficile infection (CDI) was analyzed in clinical patients and a mouse model. Materials and methods: A prospective investigation was conducted in medical wards of Tainan Hospital, Ministry of Health and Welfare, Tainan, Taiwan, from January 2011 to January 2013. Adult patients were followed up for the development of CDI. Single nucleotide polymorphisms (SNPs) of TLR2 and TLR4 were analyzed to assess the relationship between genetic polymorphisms and the development of CDI. A mouse model of CDI was used to investigate the pathogenic role of TLRs in CDI, TLR2 and TLR4 knockout (Tlr2-/- and Tlr4-/-) mice. Results: In the prospective study, 556 patients were enrolled, and 6.5% (36) of patients, accounting for 3.59 episodes per 1000 patient-days, developed CDI. Of 539 patients with available blood samples, the TLR2 rs3804099 polymorphism was more often noted in those with CDI than in those without CDI (64.5% vs. 46.1%; P = 0.046) but was not significant in multivariate analysis. Because the TLR2 rs3804099 polymorphism was moderately associated with CDI, the role of TLR2 and TLR4 was further evaluated in a mouse model. Both Tlr2-/- and Tlr4-/- mice showed more severe CDI disease than wild-type mice in terms of body weight change and fecal content five days after oral challenge with C. difficile. Furthermore, Tlr2-/- mice suffered from more severe disease than Tlr4-/- mice, as evidenced by stool consistency, cecum weight, and survival rate. Conclusion: The TLR2 rs3804099 polymorphism is marginally associated with the development of CDI, and the pathogenic role of TLR2 is further supported by a mouse model.